SLRs with point-and-shoot personalities. (PC World Philippines)
Offering live-view LCDs, scene modes, and other consumer-friendly features, digital SLRs have become almost as easy to use as the simplest point-and-shoot cameras. Some of the best new generation of SLRs, including a few high-end models that will wow the pros, were examined.